Assessment of the Impact of Monocrotophos on the Haematological and Histological Parameters of the Freshwater Fish Labeo rohita (Hamilton, 1822) - Girija, Ramankutty; Puthenpurakkal, Deepthi; Ismail, Shahila; Karpanaiselvan, Balasubramanian; Kadalmani, Balamuthu (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
This study investigated the acute sublethal toxicity of Monocrotophos on the behavioural, haematological, and histological parameters of the freshwater fish Labeo rohita. Fish exposed to Monocrotophos (10 ppm and 100 ppm) exhibited notable behavioural alterations, including loss of equilibrium, frequent surfacing, heightened mucus secretion, irregular locomotion, and erratic swimming behaviour. The 96-hour LC50 value for L. rohita was determined to be 48.50 ppm. Sub-lethal concentrations (10, 20, 40, and 60 ppm) were employed to assess the effects of acute exposure over a period of 30 days. The increase in Monocrotophos concentrations led to a consistent decrease in total RBC count and haemoglobin levels, although the total WBC count showed a proportional rise with both concentration and length of exposure. Histopathological analysis revealed significant structural damage to the gill and liver tissues in the treated fish relative to the controls. The findings highlight the substantial behavioural and physiological alterations caused by Monocrotophos exposure in L. rohita. In order to reduce the adverse impact of this chemical on aquatic ecosystems, stringent regulation and attentive application are essential.